Phenological advance in the South African Namaqualand Daisy Bloom over the past decades - Snyman, Pascal Ludwig (My University, 2024)
Climate change is driving changes in environmental suitability, competitive dynamics and phenological cycles of plants and animals. Through the analysis of the timing of phenological events the impact of climate change on plant and animal species can be measured and assessed effectively. In this study the impact of climate change on the timing of bloom of Namaqualand daisies is explored. Although the Namaqualand is described as a desolate and arid region during the summer months, the region is transformed into a wonderland of colours during the springtime flowering. Using documentary sources including newspaper archives from The Rand daily Mail, Volksblad and Die Burger as well as social media records from Flickr and iNaturalist, a phenological dataset spanning 1935-2018, including first flowering, full bloom and end of bloom dates for the Namaqualand daisies was compiled. First flowering and full bloom phenology of the Namaqualand daisies are advancing significantly at rates of 2.6d.decade-1 and 2.1d.decade-1. Climatic data, collectively spanning 1959-2018, from seven Namaqualand weather stations were individually correlated to the three flowering datasets. Calculations reveal that temperatures are increasing significantly in Namaqualand. The overall increase in temperature, from 1959-2018, for all seven assessed weather stations in Namaqualand is calculated at 1.18°C. Although no significant changes in precipitation were calculated, five out of the seven weather stations demonstrate slight decreases in precipitation over time ranging between 0.05-9.32mm from 1959-2018. The timing and amount of precipitation in the Namaqualand region is highly variable over time. For the periods spanned by both climate and phenology data, the relationships between the two were explored. Increasing temperatures are driving the calculated advances of the daisy flowering dates at statistically significant rates of change ranging from 0.01-0.11d.°C-1. The main climate drivers of Namaqualand daisy flowering phenology are winter and spring temperatures, the onset of the winter rainy season during April and May, and total winter precipitation. The rates of advance and climate drivers are broadly consistent with global phenological meta-analyses and records for the Southern Hemisphere. The advances in the timing of Namaqualand daisy flowering will have a significant impact on the tourism sector in the region, as flower viewing tours need to be prearranged months in advance.
A research report submitted in partial fulfilment of the requirement for the degree of Master of Science to the Faculty of Sciences, School of Geography, Archaeology and Environmental Science, University of the Witwatersrand, Johannesburg, 2020
Keywords: Climate change; Environmental suitability; Namaqualand